Analisis Faktor Perilaku Kaitannya dengan Permasalahan Pelayanan Kesehatan Ibu dan Anak (KIA) di Provinsi Riau - Zahtamal Zahtamal; Tuti Restuastuti; Fifia Chandra (Fakultas Kedokteran Universitas Riau, 2010)
The low of health community status for this time is still health problems in Indonesia, marked with the high maternalmortality and infant mortality rate. According to health survey, there are still many indicators of maternal, newbornand child health (MNCH), show low achievement. The aim of this study was to find the situation of MNCH servicesand to describe determining factors of the problems in Riau Province. Method of this research was a descriptive designwith quantitative and qualitative data. Result obtained in this research described that some indicators of MNCH servicesperformance were achievable and some were not. The profile of community on health behavior about maternal healthwas shown with good knowledge, neutral attitude, and good practice. Then, the profile of community health behaviorabout newborn and child health was shown with middle level of knowledge, positive attitude, and good practice. Keyperson, mostly categorized as a decision maker for health action was husband/wife. Viewed from quickly action onresponse of sick/unhealthy family members for MNCH services indicated that there was not late decision. There werestill many communities’ beliefs, not match with health value, especially for MNCH.